Molecular Detection of Cytomegalo, CDK2 and P27 in Tissues from Patients with Thyroid Carcinoma - Shakir H. Mohammed Al-Alwany (Journal of Global Pharma Technology, 2017)
Background: Thyroid cancers are related to many environmental and genetic predisposing factors. Cytomegalovirus infection may activate the protein kinase pathways, where in papillary thyroid cancer aberrant activation of these pathways is frequently associated with BRAF mutation. The bulk of thyroid cancers has maintained the expression of p27 which is the inhibitor of Cdk2.Objective: The study was designed to examine cellular dysregulation mediated by the concordant protein expressions of CDK2 and P27 tumor suppressor genes with CMV in tissues from thyroid goiter and thyroid cancers.Patients and Methods: A seventy thyroid tissues were examined for HCMV-DNA and CDK2 & P27 genes expression. Those samples belonged to ( 30) patients diagnosed with thyroid cancer and (25) thyroid goiter tissues blocks as well as (15) autopsies from apparently normal thyroid tissues. The detection of HCMV was by in situ hybridization (ISH) whereas CDK2 & P27 genes expression by immunohistochemistry (IHC). Results: HCMV DNA-ISH reaction in thyroid cancers was found in 14 / 30 (46.7%), whereas 32% (8 out of 25cases) HCMV- positivity was detected in thyroid goiter group. None of healthy thyroid tissues revealed ISH reaction. The difference of the HCMV in thyroid cancers and  control was highly significant. Detection of CDK2 in thyroid cancer was found in 13 out of 30 (43.3%) and benign thyroid goiters group was 28 % (7 out of 25). Detection of p27- expressions in thyroid cancers  in 18 out of 30 (60%) was noticed; In thyroid goiter was detected in 36% (9 out of 25) and none of the examined healthy thyroid in the control group revealed such IHC- reactions for both CDK2 &P27 IHC reactions. The difference between the percentages of CDK2- as well as P27 proteins detection in thyroid tissues & control group was statistically significant (<0.05).Conclusions: The significant detection of HCMV along with CDK2 & P27genes expression in thyroid cancer patients could support an etiologic role for that virus along with these genes in thyroid carcinogenesis.Keywords: Thyroid Cancer, HCMV, ISH, IHC, CDK2&P27.